A Quantitative MR Study of the Hippocampal Formation, the Amygdala, and the Temporal Horn of the Lateral Ventricle in Healthy Subjects 40 to 90 Years of Age - Mu, Qiwen; Xie, Jingxia; Wen, Zongyao; Weng, Yaqin; Shuyun, Zhang (American Journal of Neuroradiology, 1999)
BACKGROUND AND PURPOSE: Several investigators have defined normal age-specific values for the medial temporal lobe structures in neurologically normal elderly subjects, but, to our knowledge, no one has reported those values for a large sample of healthy volunteers. The purpose of our study was to define normal age-specific values for the hippocampal formation, the amygdala, and the temporal horn of the lateral ventricle by age group, ranging from 40 to 90 years, in order to generate a guideline for the quantitative MR diagnosis and differential diagnosis for early Alzheimer disease.METHODS: MR-based volumetric measurements of the hippocampal formation, the amygdala, and the temporal horn, standardized by total intracranial volume, were obtained from oblique coronal and sagittal T1-weighted MR images in 619 healthy volunteers and two cadaveric specimens.RESULTS: Differences in standardized volumes of the hippocampal formation, the amygdala, and the temporal horn were significant among the 61- to 70-year-old, 71- to 80-year-old, and 81- to 90-year-old groups, and were not significant between the 40- to 50-year-old and 51- to 60-year-old groups. We found no significant differences in side or sex among the age groups for any of the structures.CONCLUSION: Differences in the mean value and in the 95% normal range of standardized volumes of the hippocampal formation, the amygdala, and the temporal horn correspond to differences in age among healthy subjects; therefore, age should be considered a factor in correlative research, especially in that involving patients in the early stages of Alzheimer disease.